Ethyl 5-((1E)-1-{(E)-2-[1-(4-ethoxycarbonyl-3-methyl-1,2-oxazol-5-yl)ethylidene]hydrazin-1-ylidene}ethyl)-3-methyl-1,2-oxazole-4-carboxylate - Abdullah M. Asiri; Abdulrahman O. Al-Youbi; Hassan M. Faidallah; Seik Weng Ng; Edward R. T. Tiekink (Acta Crystallographica Section E, 2011)
The complete molecule of the title compound, C18H22N4O6, is generated by the application of a twofold axis of symmetry. Twists are evident in the molecule, i.e. between each —C=N—N group and the adjacent oxazole ring [dihedral angle = 46.08 (12) °] and between the latter and attached ester group [excluding the terminal methyl group; dihedral angle = 24.4 (7) °]. In the crystal, C—H...O and π–π [3.5990 (11) Å] contacts connect molecules into supramolecular arrays in the ac plane. These stack along the b axis, being connected by weak π–π [3.3903 (11) Å] interactions.